Moral Injury, Religiosity, and Suicide Risk in U.S. Veterans and Active Duty Military with PTSD Symptoms. Issue 3 (15th June 2018) - Ames, Donna; Erickson, Zachary; Youssef, Nagy A; Arnold, Irina; Adamson, Chaplain Sam; Sones, Alexander C; Yin, Justin; Haynes, Kerry; Volk, Fred; Teng, Ellen J; Oliver, John P; Koenig, Harold G
Abstract: Introduction: There is growing evidence that moral injury (MI) is related to greater suicide risk among Veterans and Active Duty Military (V/ADM). This study examines the relationship between MI and suicide risk and the moderating effect of religiosity on this relationship in V/ADM with post-traumatic stress disorder (PTSD) symptoms. Materials and Methods: This was a cross-sectional multi-site study involving 570 V/ADM from across the USA. Inclusion criteria were having served in a combat theater and the presence of PTSD symptoms. Multidimensional measures assessed MI, religiosity, PTSD symptoms, anxiety, and depression. In this secondary data analysis, a suicide risk index was created based on 10 known risk factors. Associations between MI and the suicide risk index were examined, controlling for demographic, religious, and military characteristics, and the moderating effects of religiosity were explored. Results: MI overall was correlated strongly with suicide risk ( r = 0.54), as were MI subscales (ranging from r = 0.19 for loss of trust to 0.48 for self-condemnation). Controlling for other characteristics had little effect on this relationship ( B = 0.016, SE = 0.001, p < 0.0001). Religiosity was unrelated to suicide risk and did not moderate the relationship between suicide risk and MI or any of its subscales. Conclusion: MI is strongly and independently associated with risk factors for suicide among V/ADM with PTSD symptoms, and religiosity does not mediate or moderate this relationship. Whether interventions that target MI reduce risk of suicide or suicidal ideation remains unknown and needs further study.